The importance of the serum quantitative levels of hepatitis B surface antigen and hepatitis B e antigen in children with chronic hepatitis B - Demirören, Kaan; Kocamaz, Halil; Doğan, Yaşar (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: We aimed to investigate the clinical importance of quantitative levels of serum hepatitis B surface antigen (HBsAg) and hepatitis B e antigen (HBeAg), and to detect their correlation with hepatitis B virus (HBV) DNA load, alanine aminotransferase (ALT) levels, hepatic activity index (HAI) and fibrosis scores. Materials and Methods: A total of 56 HBeAg-positive children with chronic hepatitis B (CHB) were included in the study. Quantification of HBsAg and HBeAg was performed using an automated chemiluminescent microparticle immunoassay. Comparisons were performed using the paired t-test, Mann-Whitney U test or t-test for independent samples. Correlations were tested using the Pearson correlation analysis. Results: Significant differences were found between groups of pre- and post treatment quantitative levels of HBsAg, HBeAg, HBV DNA, and ALT. Comparison of HBsAg, HBeAg, HBV DNA, and ALT levels before the treatment and decrease ratios of these levels after treatment according to HAI and fibrosis scores did not show any statistically significant differences. There was a positive correlation between pretreatment HBV DNA load and HBeAg levels, and a negative correlation between pretreatment HBV DNA and ALT levels. There was a negative correlation between decrease ratios of HBsAg and ALT levels after treatment. Patients with post treatment HBeAg seroconversion had a lower post treatment HBV DNA load and a higher decrease ratio of HBsAg than patients who did not have HBeAg seroconversion. Conclusion: The present study indicated that HBsAg and HBeAg levels significantly decreased during treatment and that HBeAg correlated with HBV DNA load. Quantitative HBeAg and HBsAg assays could therefore have an important role in treatment of CHB.